2013
DOI: 10.1007/s12603-013-0032-9
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of community-dwelling elderly with newly diagnosed Alzheimer's disease: Prevalence of malnutrition and the relation of various factors to nutritional status

Abstract: One in seven community-dwelling elderly with newly diagnosed AD is at risk of malnutrition. The degree of impairment in daily functioning is independently related to nutritional status. Therefore, assessment of the nutritional status should be included in the comprehensive assessment of AD patients. The relation between daily functioning, nutritional status and AD warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
1
23

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 34 publications
5
44
1
23
Order By: Relevance
“…Recent studies also utilized the MNA test cross-sectionally and longitudinally in patients with dementia (1,6,9,10). The reported rate of malnutrition among communitydwelling AD patients varies between 0% and 23.2% in different populations (7,9,(11)(12)(13). However, the rate of malnutrition was higher in our study compared to these previously published studies.…”
Section: Discussioncontrasting
confidence: 81%
“…Recent studies also utilized the MNA test cross-sectionally and longitudinally in patients with dementia (1,6,9,10). The reported rate of malnutrition among communitydwelling AD patients varies between 0% and 23.2% in different populations (7,9,(11)(12)(13). However, the rate of malnutrition was higher in our study compared to these previously published studies.…”
Section: Discussioncontrasting
confidence: 81%
“…Replication of these preliminary findings in community-based populations with more diversified demographical, socio-economic, ethnical and medical status, as well as with other biomarkers of AD, is warranted and clinical application is not justified. There is evidence that, among newly diagnosed AD patients, those at risk of malnutrition have more severe impairments of basic and complex daily functioning than well-nourished AD patients (62). These data indicate that assessment of nutritional status is valuable in the diagnostic work up of AD, and that aging individuals might benefit from nutritional interventions implemented prior to developing disease-related malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…The number of community-dwelling AD patients with weight loss described in the literature varies between 20 % and 45 % [5,13,14,21,52,55]. The number of community-dwelling AD patients at risk of undernutrition according to the mini-nutritional assessment (MNA), which is a validated screening and assessment tool to identify risk of undernutrition in older people [23,49], varies from 14 % to 80 % [8,17,21,35,36,40,41,44,48] and the number of undernourished patients (according to the MNA) varies from 0 % to 9 % [8,20,40,41]. This wide variation in the number of community-dwelling AD patients with weight loss and (risk of) undernutrition could be explained as follows: the highest prevalence of weight loss and (risk of) undernutrition were reported in studies from the precholinesterase inhibitor (ChEI) era [13,52,55].…”
Section: Epidemiology Of Weight Loss and Undernutritionmentioning
confidence: 99%
“…Even though severe undernutrition might not be an issue in communitydwelling AD patients, one in seven community-dwelling elderly people with newly diagnosed AD was at risk of undernutrition in a recently published investigation [8] and other studies reported even higher rates [17,21,35,36,40,41,44,48]. Given the suggested adverse outcomes of weight loss and (risk of) undernutrition, it is important to pay attention to the nutritional status of community-dwelling AD patients.…”
Section: Epidemiology Of Weight Loss and Undernutritionmentioning
confidence: 99%
See 1 more Smart Citation